Microbiota Induced Changes in the Immune Response in Pregnant Mice - Faas, Marijke M.; Liu, Yuanrui; Borghuis, Theo; van Loo-Bouwman, Carolien A.; Harmsen, Hermie; de Vos, Paul (Frontiers in Immunology, 2020)
Pregnancy is associated with adaptations of the immune response to accommodate the semi-allogeneic fetus and with changes in the gut microbiome. We hypothesized that the immunological adaptations may be induced by the gut microbiome. To test this hypothesis, we collected feces from pregnant conventional mice before and during pregnancy (days 7, 14 and 18) and microbiota were measured using 16S RNA sequencing. At day 18, mice were sacrificed and splenic (various Th cell populations) and blood immune cells (monocyte subsets) were measured by flow cytometry. The data were compared with splenic and blood immune cell populations from pregnant (day18) germfree mice and non-pregnant conventional and germfree mice. Finally, from conventional pregnant mice, microbiota data were correlated to immune data. The microbiome of conventional mice was significantly different at the end of pregnancy (day18) as compared with pre-pregnancy (Permanova, p<0.05). The Shannon index was decreased and the Firmicutes/Bacteroidetes ratio was increased (Friedman followed by Dunn’s test, p<0.05), while abundances of various species (such as Allobaculum stercoricans, Barnesiella intestihominis and Roseburia faecis) were significantly different at day 18 compared with pre-pregnancy. In pregnant conventional mice, the percentage of Th1 cells was decreased, while the percentages of Treg cells and Th2 cells were increased vs non-pregnant mice. In germfree mice, only the percentage of Th1 cells was increased in pregnant vs non-pregnant mice, with no effect of pregnancy on Treg and Th2 cells. The percentages of monocyte subsets were affected by pregnancy similarly in conventional and germfree mice. However, the activation status of monocytes (expression of CD80 and MHCII) was affected by pregnancy mainly in conventional mice, and not in germfree mice. Correlation (Spearman’s coefficient) of pregnancy affected microbiota with germfree and pregnancy affected immune cells showed many correlations between bacteria and immune cells. Microbiota and immune cells are affected by pregnancy in mice. Part of the immunological changes during pregnancy may be induced by the microbiome changes during pregnancy. We suggest that aberrant immune adaptations to pregnancy, such as for instance during preeclampsia, may potentially be treated with pro- or prebiotics to optimize the microbiome and therefore the immune response.